Gene Families of AmpC-producing Enterobacteriaceae Present in the Intensive Care Unit of Cipto Mangunkusumo Hospital Jakarta - Lucky Hartati Moehario; Thomas Robertus; Anis Karuniawati; Rudyanto Sedono; Delly Chipta Lestari; Andi Yasmon (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Antibiotic resistance has become a worldwide problem. Among Asia countries, Indonesia has high prevalence of multi-drug resistant organisms mainly due to Gram-negative bacilli Enterobacteriaceae. This study aimed to find out whether gene family of AmpC and AmpC/ESBL-producing Enterobacteriaceae were present in the Intensive Care Unit (ICU) of Cipto Mangunkusumo Hospital, Jakarta, Indonesia.METHODS: Specimens were obtained from several body sites of adult patients with infection hospitalised in ICU of Cipto Mangunkusumo Hospital. VITEK®2 was used to identify the microorganisms. Antibiotic susceptibility tests were conducted using VITEK®2 and disc diffusion technique according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Double disc synergy (DDS) test method was employed to detect AmpC activity. Gene families of ampC were identified using multiplex polymerase chain reaction (PCR).RESULTS: Forty five isolates were identified as putative AmpC, extended-Spectrum β-lactamases (ESBL) and AmpC/ESBL-producing Enterobacteriaceae. Klebsiella pneumoniae (n=32) were predominant, followed by Escherichia coli (n=6), Enterobacter cloacae (n=5) and Enterobacter aerogenes (n=2). AmpC activity was detected in 9 isolates, in which 4 isolates were AmpC producing and 5 isolates were AmpC/ESBL. In vitro, AmpC-producing Enterobacteriaceae showed good susceptibility to many antibiotic tested, while those of AmpC/ESBL-producing only to Amikacin. The gene families of ampC were DHA, EBC and CIT identified from 6 isolates.CONCLUSION: DHA, EBC and CIT gene families were identified from AmpC and AmpC/ESBL-producing Enterobacteriaceae in the ICU of Cipto Mangunkusumo Hospital. While the AmpC-producing was still susceptible to almost all antibiotics tested, the AmpC/ESBL-producing showed resistant except for Amikacin.KEYWORDS: Enterobacteriaceae, β-lactamases, AmpC, ESBL